Co-growth of Stem Cells With Target Tissue Culture as an Easy and Effective Method of Directed Differentiation - Kovina, Marina Valentinovna; Dyuzheva, Tatyana Gennadievna; Krasheninnikov, Mikhail Evgenievich; Yakovenko, Sergey Alexandrovich; Khodarovich, Yury Mikhailovich (Frontiers in Bioengineering and Biotechnology, 2021)
The long-term coculture of mouse embryonic stem cells (mESC) with rat endothelial cells (EC) was tested for contact differentiation into the endothelial lineage. Serial passaging of rat ECs mixed with mESC in ratio 10:1 resulted in the emergence of a homogeneous cell population expressing mouse endothelial surface markers CD102, CD29, CD31. Rat endothelial surface marker RECA-1 completely disappeared from the cocultured population after 2 months of weekly passaging. Co-incubation of mESC with rat ECs without cell-to-cell contact did not result in the conversion of mESC into ECs. After cocultivation of adult mesenchymal stem cells from human endometrium (eMSC) with pre-hepatocyte-like cells of human hepatocarcinoma Huh7 the resulting coculture expressed mature liver markers (oval cell antigene and cytokeratine 7), none of which were expressed by any of co-cultivated cultures, thus proving that even an immature (proliferating) pre-hepatocyte-like line can induce hepatic differentiation of stem cells. In conclusion, we have developed conditions where long-term co-proliferation of embryonic or adult SC with fully or partially differentiated cells results in stem cell progeny expressing markers of target tissue. In the case of endothelial differentiation, the template population quickly disappeared from the resulted culture and the pure endothelial population of stem cell progeny emerged. This approach demonstrates the expectable fate of stem cells during various in vivo SC-therapies and also might be used as an effective in vitro differentiation method to develop the pure endothelium and, potentially, other tissue types of desirable genetic background.